2011
DOI: 10.1074/jbc.m110.206136
|View full text |Cite
|
Sign up to set email alerts
|

Heme Interacts with C1q and Inhibits the Classical Complement Pathway

Abstract: C1q is the recognition subunit of the first component of the classical complement pathway. It participates in clearance of immune complexes and apoptotic cells as well as in defense against pathogens. Inappropriate activation of the complement contributes to cellular and tissue damage in different pathologies, urging the need for the development of therapeutic agents that are able to inhibit the complement system. In this study, we report heme as an inhibitor of C1q. Exposure of C1q to heme significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 54 publications
1
41
2
Order By: Relevance
“…Further, formation of a C1q-heme complex changed the mechanisms of recognition of IgG and CRP. 200 Binding of ferric heme to C1q was accompanied by an increase in the absorption at 400-405 nm ( Figure 13). Direct titration with hemin showed that the binding stoichiometry was 12 hemes per C1q molecule.…”
Section: R Immunoglobulin G and C1qmentioning
confidence: 96%
See 2 more Smart Citations
“…Further, formation of a C1q-heme complex changed the mechanisms of recognition of IgG and CRP. 200 Binding of ferric heme to C1q was accompanied by an increase in the absorption at 400-405 nm ( Figure 13). Direct titration with hemin showed that the binding stoichiometry was 12 hemes per C1q molecule.…”
Section: R Immunoglobulin G and C1qmentioning
confidence: 96%
“…200 Based on these results, it was proposed that heme could function as a natural inhibitor of the complement pathway, an activity that will be exacerbated under conditions of excessive tissue damage and hemolysis, where large amounts of heme are released into the circulation. 200 Molecular communication between proteins and their interacting partners underlies the rich biochemistry of living organisms. 201 About 20% of human antibodies bind heme as an interface cofactor.…”
Section: R Immunoglobulin G and C1qmentioning
confidence: 97%
See 1 more Smart Citation
“…Heme induces an oxidative stress and stimulates the EC via TLR4, leading to vWF and P‐selectin expression . Heme is also a direct activator of the C3 convertase and can stimulates the alternative but inhibits the classical pathway in vitro and in vivo in a mouse model of hemolysis (N. Merle and L. Roumenina, unpublished). Aside from inducing a pro‐thrombotic phenotype and activating complement heme inhibits ADAMTS‐13 activity, or activation of coagulation cascade .…”
Section: Endothelial Cells As a Target In Ahusmentioning
confidence: 99%
“…Upon binding of Fe III heme to C1q the mechanism of recognition between immunoglobulin G and C‐reactive protein changes. This leads to reduced binding and thus prevents activation of further complement compounds 42a. In vitro studies of the interaction of recombinant blood coagulation factor VIII and Fe II/III heme revealed an inhibitory effect 43.…”
Section: Heme As An Essential Component In Hemoproteinsmentioning
confidence: 99%